PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK COKLAT PADA PT. PERMATA NIAGA MEDAN - Ris Novalia Jelita; Demak Claudia Yosephine Simanjuntak (LPPM UNIVERSITAS BINA INSAN, 2020)
The object of the study is PT. Permata Niaga Medan. The object was chosen because there was a decrease in purchasing decision in this company. The decrease in purchasing decision was initiated with a decrease in sales in the company. The decreased sales was affected by promotion and product quality in the company. The inactive promotion could be seen from the promotion frequency and the decrease in product quality could be seen from the return of chocolate by consumers. The research used some theories relating to marketing management relating to promotion, product quality, and purchasing decision. Data were collected through interview, questionnaires and documentation. The data analysis method used was multiple linear regresion analysis, determination coefficient of simultaneous testing (F-testing) and partial testing (T-test). The research populations were 186 consumers with 128 samples. The simultaneous testing showed that promotion and product quality had a positive and significant effect on purchasing decision of chocolate products at PT. Permata Niaga Medan with the determination coefficient of 39.7% whle the remaining 60.3% was explained by other independent variables not researched such as service quality, price, and brand. Based on the result of the research, it is concluded that promotion and product quality had a significant effect on purchasing decision of chocalate products at PT. Permata Niaga Medan.